Serviço Social e Responsabilidade Social: Uma análise do conhecimento fomentado nos cursos presenciais do Rio Grande do Norte - Gurgel, Ferdinanda Fernandes (2017)
Organizations have been defied to adopt actions or behaviors in benefit of their own collaborators or the society at large, instead of aiming profit only. This consciousness or set of attitudes is defined as Social Responsibility, which has become a requirement of survival in a competitive market. In Brazil, it became prominent in 1980 when some companies decided to embrace the idea due to working class claims and the Societal Movement. Consequently, the business class started defining strategies to reconcile private and collective interests, whereas professions and respective curricula had to adapt themselves in order to respond to the emerging demands. And this also applies to Social Work. In this sense, the general objective of this study is: To understand how the knowledge on Social Responsibility is part of presential undergraduate courses in Social Work in Rio Grande do Norte state. As specific objectives: To analyze the pedagogical project of presential undergraduate courses in Social Work in Rio Grande do Norte state, seeking to perceive the Social Responsibility bias; Assess the conception of Social Responsibility in the discourse of coordinators and professors of presential undergraduate courses in Social Work in Rio Grande do Norte state; Verify the perception of Social Work students in Rio Grande do Norte state about the theme and professional formation, in relation to Social Responsibility. Regarding the methodological aspects, this study is qualitative in nature, including both documentary and field researches; yet, for descriptive purposes, quantitative data was collected. The study involved 148 participants: five course coordinators, six professors and 137 students of the last semester of six presential undergraduate courses in Social Work across Rio Grande do Norte state, offered by either private or public institutions, which are located in the cities of Mossoró (2), Assu (1), Caicó (1) and Natal (2). Semi-structured interviews were conducted with professors and coordinators, while closed questionnaires with students, aside from fieldwork diary. All interviews were taped and transcribed, as explained in the Informed Consent signed by each participant. Then, interpretative analysis of the interviews and quantitative data took place. The results demonstrate that the theme of Social Responsibility occurs only transversely in the Pedagogical Projects and Curricula Matrices, inside specific topics in either compulsory or optional subjects. Moreover, the theme neither appears clear and objectively in the speeches of coordinators or professors nor bounces during internal discussions, indicating its secondary character in the programs, which leads to a lack of academic productions, despite the recognized market demand. Notwithstanding, students manifest they understand Social Responsibility as something more comprehensive, beyond the charity practices, that aims to balance the organization from the ethical, legal and economical perspectives. However, they highlight the need for a theoretical deepening in the area, by teaching, research or extension